Constantine Calafateanu, the greatest artist of romanian modern art - Marković, Kamenko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Constantine Calafateanu (1911–1978) is one of the most important Romanian painters of the twentieth century. He studied French literature at the Sorbonne, but he also regularly visited two painting studios: La Grande Chaumiere and Julien Academy. On returning to Romania he did some teaching work, therefore, he started exhibiting relatively late in life. His first solo exhibition took place in 1965. The creation of this painter highlights two phases: the first one lasted until 1965 and the second one lasted from 1968 to the end of the painter’s life. Calafateanu mostly painted landscapes (fall and winter), flowers, still life, and nudes.